Resiliensi Guru PAI dalam Mengembangkan Kemampuan Adaptif pada Era Society 5.0 di SMP Asy-Syafi’iyah Lohgung Brondong - Sisfiana Ajeng Anggraeni; Fathul Amin (JIMAD: Jurnal Ilmiah Mutiara Pendidikan, 2026)
The development of education in the Society 5.0 era has introduced new challenges for Islamic Religious Education (PAI) teachers through the integration of digital technology, changes in students’ characteristics, and increasing demands for innovative and adaptive learning, particularly in schools with limited facilities. This study aims to analyze PAI teachers’ understanding of resilience, the forms of resilience they develop, and its relevance to adaptive learning competencies at SMP Asy-Syafi’iyah Lohgung Brondong. The study employed a phenomenological qualitative approach with a case study design. Data were collected through observation, semi-structured interviews, and documentation involving PAI teachers, the school principal, and curriculum personnel selected purposively. The findings reveal that PAI teachers perceive resilience as the ability to endure, adapt, and remain productive in responding to digital educational changes through emotional, spiritual, social, and professional strengths. Resilience is manifested through the use of digital media, individualized learning assistance, and collaboration with schools and students’ families. The study concludes that resilience plays a crucial role in strengthening teachers’ adaptive capacities by fostering innovation, openness to change, and more communicative learning practices. The novelty of this research lies in the finding that the resilience of PAI teachers in coastal schools functions not merely as a coping mechanism against educational pressures but also as the primary foundation for developing adaptive learning in the Society 5.0 era. These findings underscore the necessity of strengthening resilience through continuous professional development, institutional support, and digital literacy to ensure that PAI learning remains relevant and adaptive.